Media Sosial Pemanfaatan Media Sosial sebagai Sarana Pemasaran pada Tempat Wisata Kampoeng Kita di Desa Kertarahayu, Setu, Bekasi, Jawa Barat - Alika, Azzahra Putri (Journal of Tourism and Creativity, 2022)
Abstract Every human being on this erath, especially Indonesia must have had sosial media. They have social media for various purposes starting from small things, like making entertainment, to big things, like helping the economy. With the enormity of the the impact of social media, every human being must take a good impact and also benefit himself and his environment. This study uses a descriptive method that will discuss the facts that occur at this time. Keywords: utilization, social media, marketing